HEPATIC AND HEMATOLOGICAL ACTIVITIES OF HYDRO-ALCOHOLIC EXTRACT OF ERIOBOTRYA JAPONICA FRUITS IN SWISS ALBINO MICE - SABEEHA SHAFI; NAHIDA TABASSUM (International Journal of Pharma and Bio Sciences, 2015)
The hydro-alcoholic extract of fruits of Eriobotrya japonica was evaluated for its toxicity on hepatic and hematological parameters in swiss albino mice. Animals of either sex were treated with different doses of the extract for its acute toxicity tests. The doses taken were 500,1000,1500,2000 mg/kg. In this LD50 was calculated. After finding the LD50, optimum dose for sub-acute toxicity studies were taken. The effect of the plant extract on hepatic and hematological parameters were taken into consideration. The doses taken were 250 and 500 mg/kg b.w. Histopathology of liver and spleen were also done. The results shows that in acute toxicity studies, it showed that LD50 was 500mg/kg b.w and in sub-acute studies it showed variable biochemical parameters with no toxicity on liver and spleen.